THE ANALYSIS OF FOLLOW-UP SUPERVISION OF EARLY CHILDHOOD EDUCATION UNITS IN BANTEN 2021 - Yanti Puspita (Jurnal Ilmiah Visi, 2022)
Implementing supervision for early childhood units is a coaching effort aimed at improving educational quality. Educational monitoring was carried out by the Early Childhood Education Development and Community Education Center in 2021 using two methods: online supervision in the form of google drive document link and youtube connections, and offline supervision in the form of support to each early childhood unit. The goal of this study is to make recommendations for how to address any shortcomings that arise in the implementation of educational supervision in 2021. A descriptive qualitative technique is used in this study. The data was collected using the data triangulation approach (observation, interview and study of documentation). Data reduction, data collecting, data presentation, and conclusion drawing are all stages of data analysis. The study's findings demonstrate that the manager's online supervision capacity exceeds the existing supervision quota. The quota of online supervision respondents is 2011 institutions and the offline supervision quota is 1920. In practice, the managers had trouble uploading the needed data, which came in the form of Google Drive links for files and Youtube URLs for performance videos. The challenge faced by each institution is the presence of educators and educational professionals who have not yet fully grasped the usage of technology.Therefore stakeholders need to pay more attention to improving the quality of human resources in early childhood edecation units, especially in terms of utilizing technology. Keywords: Education supervision, Early Childhood Education